Digitalisasi Umkm dalam Inovasi Pemasaran Produk dan Pembayaran Digital pada Pelaku Industri Rumahan di Desa Kronjo Kabupaten Tangerang Provinsi Banten - Dedy Khaerudin; Irma Nurmala Dewi; Ganjar Sidik Gandara; Tito Juan; Aulia Putri (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
The home industry business actors in Kronjo Village boast a diverse range of high quality products, including processed fishery products and processed products derived from mangrove forests. Despite the abundance of these products, a significant number of individuals, both local and domestic, remain unaware of them. The market has not yet fully embraced these products, and occasionally, there are challenges when it comes to providing refunds to consumers during manual transactions. This community service initiative aims to impart comprehensive information to MSME industry participants on marketing innovations and digital payments within their respective enterprises. The provision of training is expected to enhance the ability of home industry players to promote their products and effectively use digital payment systems for transaction facilitation. Consequently, this activity enables participants in the home industry to enhance their revenue and understand that payments can be conducted digitally, specifically through QRIS or unique payment codes, rather than just in cash or transfers between banks.